205k views
4 votes
Why is the solution to this equation 3(95-6x)=x-152

User MatrixTXT
by
5.4k points

2 Answers

1 vote

3(95 - 6x) = x - 152

First we work out the brackets.

285 - 18x = x - 152

Now we collect terms

- 19x = - 437

Finally we divide both sides by -19 to find out our answer.

x = 23
User JorgeeFG
by
7.0k points
3 votes
you would distribute the 3 to 95 and -6x and you would get 285-18x=x-152, then you would subtract x from both sides and you would get 285-19x= -152, then you would subtract 285 from both sides and you would get -19x= - 437, then you divide both sides by -19 and you would get x= 23
User Sleiman Jneidi
by
5.7k points